The Distinction Between Semantic and Pragmatic Meaning With reference to the third year students - Dept. of English, College of Basic Education: A Practical study (Journal of the College of Basic Education, 2022)
Pragmatics and Semantics are inter-related subjects and the distinctionbetween them is necessary to provide a framework for explaining the variety ofways in which what a speaker conveys can fail to be fully determined by the(conventional) linguistic meaning of the sentence he utters. In a more positive vein, the distinction between semantics and pragmaticshas served to separate strictly linguistic facts about utterances from those thatinvolve the actions, intentions, and inferences of language users (speaker-hearers). However, there are some linguistic phenomena that seem to straddlethe semantics-pragmatics boundary.